Pseudorapidity distributions of charged hadrons in proton-lead collisions at $\sqrt{s_{_NN}} =$ 5.02 and 8.16 TeV - CMS collaboration (2258 authors) (2018)
The pseudorapidity distributions of charged hadrons in proton-lead collisions at nucleon-nucleon center-of-mass energies $ \sqrt{s_{NN}}=5.02 $ and 8.16 TeV are presented. The measurements are based on data samples collected by the CMS experiment at the LHC. The number of primary charged hadrons produced in non-single-diffractive proton-lead collisions is determined in the pseudorapidity range |η$_{lab}$| < 2.4. The charged-hadron multiplicity distributions are compared to the predictions from theoretical calculations and Monte Carlo event generators. In the center-of-mass pseudorapidity range |η$_{cm}$| < 0.5, the average charged-hadron multiplicity densities 〈dN$_{ch}$/dη$_{cm}$〉$_{|η}_{cm|}$ < 0.5 are 17.31 ± 0.01 (stat) ± 0.59 (syst) and 20.10 ± 0.01 (stat) ± 0.85(syst) at $ \sqrt{s_{NN}}=5.02 $ and 8.16 TeV, respectively. The particle densities per participant nucleon are compared to similar measurements in proton-proton, proton-nucleus, and nucleus-nucleus collisions.